2010
DOI: 10.1016/j.drup.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside modifying enzymes

Abstract: Aminoglycosides have been an essential component of the armamentarium in the treatment of lifethreatening infections. Unfortunately, their efficacy has been reduced by the surge and dissemination of resistance. In some cases the levels of resistance reached the point that rendered them virtually useless. Among many known mechanisms of resistance to aminoglycosides, enzymatic modification is the most prevalent in the clinical setting. Aminoglycoside modifying enzymes catalyze the modification at different −OH o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
1,095
0
21

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,122 publications
(1,153 citation statements)
references
References 331 publications
(330 reference statements)
37
1,095
0
21
Order By: Relevance
“…The analysis of aminoglycosides resistance in our survey indicated that ST195 isolates carry the genetic determinants aph(3")-Ib, aph(3')-Ic, aph(6)-Id [22] and armA 16S-RNAmethylase [23] and ST281 presented the same genes showed above with the addition of aadA1. These genetic determinants explained the resistance to all the aminoglycosides tested AK, GM, TO.…”
Section: Resistomasupporting
confidence: 57%
“…The analysis of aminoglycosides resistance in our survey indicated that ST195 isolates carry the genetic determinants aph(3")-Ib, aph(3')-Ic, aph(6)-Id [22] and armA 16S-RNAmethylase [23] and ST281 presented the same genes showed above with the addition of aadA1. These genetic determinants explained the resistance to all the aminoglycosides tested AK, GM, TO.…”
Section: Resistomasupporting
confidence: 57%
“…AadA1 has aminoglycoside 3¢-adenylyltransferase activity which is associated with streptomycin and spectinomycin resistance. AacC1 gentamicin 3¢-acetyltransferase conveys resistance to gentamicin only (Ramirez et al, 2010). High prevalence of aacC1 gene associated with class 1 integron in MDR isolates may be due to inordinate prescription of aminoglycosides in clinical settings and might also be due to a clonal spread of one A. baumanni clone.…”
Section: Discussionmentioning
confidence: 99%
“…Aminoglycoside resistance genes confer resistance to this class of antibiotics by different modifying enzymes, including phosphotransferases (aphA1 and aphA6), nucleotidyltransferases (aadA1 and aadB) and acetyltransferase (aacC1) (Ramirez & Tolmasky, 2010). In addition, intrinsic resistance to all these antibiotics could occur by means of general AdeABC efflux pumps (adeB) (Yoon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%